Work Schedule Patching in Health Care: Exploring Implementation Approaches. Issue 2 (May 2020) - Kossek, Ellen Ernst; Rosokha, Lindsay Mechem; Leana, Carrie
The authors propose a typology of "work schedule patching, " the ongoing adjustments made to plug scheduling holes after employers post schedules. Patching occurs due to changes in employer work demands, or employee nonwork demands necessitating scheduling adjustments, which are reactive or proactive. Using qualitative data from eight health-care facilities, the authors identified three narratives justifying schedule patching implementation approaches (share-the-pain, work-life-needs, and reverse-status-rotation) with variation in formalization and improvisation. Exploratory analysis showed a suggestive link between improvised work–life scheduling and lower pressure ulcers. This article advances theory on balancing the "service triangle" of scheduling in-service economies including health care.